KULIAH MELALUI WHATSAPP (KULWAPP) - Ryan Angga Pratama (De Fermat : Jurnal Pendidikan Matematika, 2019)
This study aims to describe the implementation of collaborative learning online through WhatsApp Messenger (WA) Group. The subjects in this study were 34 students of Mathematics Education at the University of Balikpapan who were studying the Theory of Numbers. Data collection techniques are carried out by observation (observation of chat activities within the WA Group), documentation, and learning outcomes tests. However, the results showed that the implementation of online learning through the WA Group went well. This can be seen from the achievement of student learning outcomes which shows that 27 out of 34 students get scores above 70. In addition, students also feel that they have new learning experiences, can express themselves in discussions, the atmosphere of learning is very relaxed, learning becomes more update, and can be accessed anywhere if students forget the material they have learned.